Konsep dan Implementasi Model Pengelolaan Kelas Berbasis Humanistik - Nasya Putry Kusumah; Najwa Meiga Azzahra; Najwa Yumna Mahira; Naila Tsuraya Zahra; Natalina Aritonang; Sofyan Iskandar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the concept and implementation of humanistic-based classroom management as a response to learning conditions that remain teacher-centered and limit students’ opportunities to develop their potential. The purpose of this research is to analyze theoretical foundations of humanistic learning and to identify ways in which these principles can be applied to classroom management at the elementary school level. The study employs a qualitative method with a literature review approach, gathering data from books, scientific journals, and relevant academic documents published within the last five years. The data were analyzed using content analysis techniques to identify themes and patterns related to humanistic approaches in classroom management. The findings indicate that classroom management grounded in humanistic principles emphasizes the creation of a safe, supportive, and meaningful learning environment that recognizes students as unique individuals with diverse emotional, social, and cognitive needs. Its implementation encourages students to become independent, creative, collaborative, and capable of self-actualization. Overall, this model has been shown to be effective in enhancing active participation, strengthening teacher–student relationships, and fostering holistic student development in elementary schools.